Dialect Language tn the Film Home Sweet Loan - Irna Inayatul Hidayah; Otong Setiawan Djauhari (INDO PUBLISHING, 2025)
This research investigates the sociolinguistic roles of dialect and language variation in the Indonesian film Home Sweet Loan (2023), focusing on how informal expressions, regional dialects, and code-switching reveal characters' identities, emotions, and social positions. Using a descriptive qualitative method, data were collected through transcription and analysis of selected scenes featuring the main character, Kaluna. Findings indicate that linguistic choices—such as Jakarta slang, Javanese/Sundanese particles, sarcastic wordplay, and metaphor—are strategically used to portray economic struggle, gender roles, emotional fatigue, and generational pressure. The study concludes that dialects in Home Sweet Loan are more than just stylistic devices; they are critical tools for expressing urban identity, navigating socioeconomic realities, and challenging traditional norms through humor, irony, and resistance.